2021
DOI: 10.3390/polym14010017
|View full text |Cite
|
Sign up to set email alerts
|

Effect of the Glass Fiber Content of a Polybutylene Terephthalate Reinforced Composite Structure on Physical and Mechanical Characteristics

Abstract: This work presents the influences of glass fiber content on the mechanical and physical characteristics of polybutylene terephthalate (PBT) reinforced with glass fibers (GF). For the mechanical characterization of the composites depending on the GF reinforcement rate, tensile tests are carried out. The results show that increasing the GF content in the polymer matrix leads to an increase in the stiffness of the composite but also to an increase in its brittleness. Scanning Electron Microscope analysis is perfo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 13 publications
0
3
0
Order By: Relevance
“…The values of G E and S E presented in table 3 were calculated using equations (7) and (9). In equation (8), the calculated data in the coordinates lnγ 1…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The values of G E and S E presented in table 3 were calculated using equations (7) and (9). In equation (8), the calculated data in the coordinates lnγ 1…”
Section: Resultsmentioning
confidence: 99%
“…When the polymer absorbs liquid, the blanket deformation is largely restricted due to a strong mechanical bond of the cellulose fibers with an elastic polymer coating, and the swelling anisotropy can increase significantly. Therefore, an a priori assessment of the impact of the liquid medium on the structure and mechanical properties [8] in terms of the solubility parameter [9] or the Flory-Huggins interaction parameter [10] may be incorrect. Theoretical and experimental studies of the sorption and swelling of crosslinked carbonchain polymers in liquid media have been carried out using macroscopic methods such as rheological and mechanical tests for cyclic compression and measurement of equilibrium swelling [6,11].…”
Section: Introductionmentioning
confidence: 99%
“…950 MPa. In the case of PBT, the range of the results reported for the elastic modulus was even greater: from 2.3 GPa obtained by Hamlaoui et al [38] up to 8 GPa reported by Borges et al [39]. It should be noted, however, that published data (averaged at the macroscopic level) cannot be directly related to those obtained using nanomechanical mapping due to the non-homogeneity of the samples observed at the nanoscale.…”
Section: S Q [Nm]mentioning
confidence: 87%
“…Коэффициент чувствительности к деформации (GF) тензодатчика с наночастицами серебра в эластичной матрице, полученного в работе [10] составляет на начальном этапе растяжения 270, а датчика при большей относительной деформации 110. Тензодатчики и датчики деформациис высоким коэффициентом GF полученным за счет монолитной интеграции растяжимой подложки с изменяющейся жесткостью и чувствительной пленки, содержащей перколяционную сеть из нанопроволок серебра признаны соответствующими эксплуатационным требованиям гибкой электроники [17][18]. При этом параметров тензочувствительности, т. е. изменению электрического сигнала при изменении механического напряжения в указанных статьях не приводится.…”
Section: Discussionunclassified